Functionalized Graphene Derivatives: Antibacterial Properties and Cytotoxicity. (14th February 2019) - Valentini, Federica; Calcaterra, Andrea; Ruggiero, Vincenzo; Pichichero, Elena; Martino, Assunta; Iosi, Francesca; Bertuccini, Lucia; Antonaroli, Simonetta; Mardente, Stefania; Zicari, Alessandra; Mari, Emanuela; Iovenitti, Giulia; et al.
Abstract : In this work, the authors prepared and characterized two different graphene oxides: one chemically synthesized (GO sample) and the other one electrochemically synthesized (GO(LiCl) ). Both samples were fully characterized with atomic force microscopy (AFM), Raman and Fourier transform infrared (FTIR) spectroscopies, X-ray photo electron spectroscopy (XPS), thermal analysis (TG/DTA), andZ -potential. The antibacterial properties of both graphene oxides were studied using Gram-negative Escherichia coli ATCC 25922 and Gram-positive Staphylococcus aureus ATCC 25923 by spectrophotometer and viable cell count as indirect and direct methods, respectively. Results demonstrated that the GO(LiCl) exhibited a significant antibacterial activity compared to GO that showed a bacteriostatic effect on both pathogens. Electron microscopy analysis confirmed the antibacterial effects of both graphene oxides toward the pathogens, especially working at 80 μ g/mL, for 24 h. Additional studies were also performed and both GO samples were not cytotoxic at 2 μ g/mL toward neuroblastoma cells. Moreover, 2 μ g of GO was suitable to carry the minimum effective dose (5.74 ng/mL) of kinase inhibitor S29 (1-(2-chloro-2-(4-chlorophenyl)ethyl)-N-(4-fluorobenzyl)-1 H -pyrazolo[3, 4- d ] pyrimidin-4-amine), providing negligible side effects related to the S29 treatment (this latter being specifically active on the neuroblastoma cell lines (SK-N-BE(2))).